2002
DOI: 10.1074/jbc.m200283200
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Helix-Loop-Helix Factor, HAND2, Functions as a Transcriptional Activator by Binding to E-boxes as a Heterodimer

Abstract: HAND2 (dHAND) is a basic helix-loop-helix (bHLH)transcription factor expressed in numerous tissues during development including the heart, limbs, and a subset of neural crest derivatives. Functional analysis has shown that HAND2 is involved in development of the branchial arches, heart, limb, vasculature, and nervous system. Although it is essential for development of numerous tissues, little is known about its mode of action. To this end, we have characterized HAND2 transcriptional regulatory mechanisms. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 40 publications
1
72
0
Order By: Relevance
“…3A). Other researchers have also found that transfections with dHAND alone cannot significantly activate transcription of luciferase promoters (6,19). Therefore, it does not appear that dHAND can activate the transcription of the luciferase gene or the flanking sequences.…”
Section: Dhand Interacts Independent Of Dna Bindingmentioning
confidence: 98%
See 3 more Smart Citations
“…3A). Other researchers have also found that transfections with dHAND alone cannot significantly activate transcription of luciferase promoters (6,19). Therefore, it does not appear that dHAND can activate the transcription of the luciferase gene or the flanking sequences.…”
Section: Dhand Interacts Independent Of Dna Bindingmentioning
confidence: 98%
“…Class I bHLH proteins (E12 and E47) are expressed ubiquitously in all tissues and can function as homodimers, but prefer to form heterodimers with other bHLH proteins (5). Class II proteins (dHAND, NeuroD, and MyoD) are expressed in specific tissues and are believed to be functionally active when complexed with a class I protein (5,6). dHAND/HAND2 (deciduum, heart, autonomic nervous system, and neural crest cell derivatives) is a 30-kDa member of the class II bHLH protein family (7,8) and has been detected in Xenopus, zebrafish, chicks, mice, and humans (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several bHLH proteins bind their targets when activated by another protein partner (for example, see Refs. [43][44][45]. If there is direct interaction between FER and the Lenramp1 promoter we predict that FER requires for transcriptional activation the interaction with a root-specific binding partner.…”
Section: Fig 2 Complementation Of Yeast Strain Smf1⌬ With Lenramp1 mentioning
confidence: 99%